Odpowiedzi

Najlepsza Odpowiedź!
2009-11-21T22:19:24+01:00
2(x+2y)² - (x-y)² +x=(x+y)(x-y)+8y²+5+10xy
3x-4y=5

2(x²+4xy+4y²)-(x²-2xy+y²)+x=x²-y²+8y²+5+10xy
3x-4y=5

2x²+8xy+8x²-x²+2xy-y²+x-x²+y²-8y²-5-10xy=0
3x-4y=5

po skróceniu zostaje
x-5=0 z tego wynika, że x=5

3*5-4y=5
4y=15-5
y=2,5
2009-11-21T22:31:34+01:00

2(x+2y)²-(x-y)²+x=(x+y)(x-y)+8y²+5+10xy
3x-4y=5

2(x²+4xy+4y²)-(x²-2xy+y²)+x=x²-y²8y²+5+10xy
3x-4y=5

2x²+8xy²+8y²-x²+2xy-y²+x=x²-y²+8y²=5=10xy
3x-4y=5

x=5
3x-4y=5

15-4y=5
10=4y
y=2,5
2009-11-21T22:38:37+01:00
2(x+2y)² - (x-y)² +x=(x+y)(x-y)+8y²+5+10xy
3x-4y=5

x=5
3x-4y=5

15-4y=5
10=4y
y=2,5
x=5